Nanotechnology - Shanmugam, S (Chennai : MJp, 2011)
Nanochemistry Nanophysics Nanoelectronics Molecular Machine Molecular Manufacturing Nanomedicine and Nanobiology Instruments and Methodology Environmental and Social Issues Basic Information Extensive Coverage Step-by-step Explanation Includes Modern Developments Explores Future Aspects Application-oriented Topics Appendices Glossary Chapter-end References Index
Includes bibliographical references, Glossary 249-260p.and Index 261-274p.
Keywords: Nanotechnology; Physics; NANO SCIENCE